The Blueprint: A Novel - Rashad, Rae Giana (New York, NY : Harper, 2024)
"Solenne Bonet is DoS--a Descendant of Slave--and has always known that her destiny would be in the service of men. At school, it is what she has been trained for, waiting for an algorithm to assign her to a white man, one of the thousands who sign up to be contract holders. She knows that there are girls who hope to be more than Maid or Mammy, who whisper about how they will get a white man to sign their freedom, how they will be sweet, but not sweet enough that he would be tempted to keep her for good. After her mother pulls strings to get Solenne an assignment as a Council archivist, Solenne attracts the attention of Bastien LeBlanc, a high-ranking white government official and rising star in the Order. He promises to make Solenne his wife, and more importantly, to grant her freedom. She is flattered by his attention and entranced by Bastien's world of power and influence--even if it means ignoring Bastien's beliefs about the need to keep her fellow DoS under strict legislation. She convinces herself that his love is enough, that he will grant her freedom. Five years later, nothing has changed. Solenne is still with Bastien--his lover, his speechwriter, his possession. When he denies her the freedom he promised, she must decide whether to stay or run"
Keywords: Dystopian fiction